FACTORS AFFECTING ACCOUNTING INFORMATION SYSTEMS IN MICRO, SMALL AND MEDIUM ENTERPRISES IN BATAM CITY - Jamie Ramadhan; Sunarto Wage (Jurnal Ekonomi, 2023)
This study the authors used a quantitative approach. The population used in this study is MSME actors in Batam City who are registered with the Batam City Cooperative and MSME Office. Data on the number of MSMEs in 2022 are 282 MSMEs. Researchers used a non-probability sampling technique, and the sampling technique used was purposive sampling. Based on calculations using the slovin formula, the sample in this study was 165 respondents. The data source in this study is primary data, this data is obtained directly from such as distributing questionnaires through the Google form. The results of this study have been carried out by researchers who found that the first hypothesis indicates that accounting knowledge has a partially significant effect on the use of accounting information in MSMEs in Batam City. The second hypothesis shows that length of business has a partially significant effect on the use of accounting information for MSMEs in Batam City. The third hypothesis shows that the owner's perception has a significant effect partially on the use of accounting information on MSMEs in Batam City. The fourth hypothesis states that accounting knowledge, length of business and owner's perceptions simultaneously have a significant effect on the use of accounting information on MSMEs in Batam City.